Phosphoproteomic Analysis of Cell-Based Resistance to BRAF Inhibitor Therapy in Melanoma - Parker, Robert; Vella, Laura J.; Xavier, Dylan; Amirkhani, Ardeshir; Parker, Jimmy; Cebon, Jonathan; Molloy, Mark P. (Frontiers in Oncology, 2015)
The treatment of melanoma by targeted inhibition of the mutated kinase BRAF with small molecules only temporarily suppresses metastatic disease. In the face of chemical inhibition tumor plasticity, both innate and adaptive, promotes survival through the biochemical and genetic reconfiguration of cellular pathways that can engage proliferative and migratory systems. To investigate this process high-resolution mass spectrometry was used to characterize the phosphoproteome of this transition in vitro. A simple and accurate, label-free quantitative method was used to localize and quantitate thousands of phosphorylation events. We also correlated changes in the phosphoproteome with the proteome to more accurately determine changes in the activity of regulatory kinases determined by kinase landscape profiling. The abundance of phosphopeptides with sites that function in cytoskeletal regulation, GTP/GDP exchange, Protein Kinase C, IGF signaling and melanosome maturation were highly divergent after transition to a drug resistant phenotype.